Thermomechanical interactions due to laser pulse in microstretch thermoelastic medium - Kumar, R.; Kumar, A.; Singh, D. (Archives of Mechanics, 2015)
The present investigation deals with deformation in microstretch generalized thermoelastic medium subjected to thermomechanical loading induced by thermal laser pulse. The Laplace and Fourier transform techniques are used to solve the problem, and concentrated normal force and thermal source describe the application of this approach. The closed form expressions of normal stress, tangential stress, couple stress, microstress and temperature distribution are obtained for the transferred domain. The numerical inversion technique of Laplace transform and Fourier transform has been applied to obtain the resulting quantities in the physical domain after developing a computer program. Normal stress, tangential stress, coupled stress and microstress temperature distribution are depicted graphically to show the microstretch effect. Some particular and special cases of interest are gathered and presented in the investigation.